\input{"/home/zack/Notes/Latex/preamble.tex"} \let\Begin\begin \let\End\end \newcommand\wrapenv[1]{#1} \makeatletter \def\ScaleWidthIfNeeded{% \ifdim\Gin@nat@width>\linewidth \linewidth \else \Gin@nat@width \fi } \def\ScaleHeightIfNeeded{% \ifdim\Gin@nat@height>0.9\textheight 0.9\textheight \else \Gin@nat@width \fi } \makeatother \setkeys{Gin}{width=\ScaleWidthIfNeeded,height=\ScaleHeightIfNeeded,keepaspectratio}% % Create indices up front \makeindex[title=Concept index] \title{ \textbf{ Title } } \author{D. Zack Garza} \date{\today} \begin{document} \maketitle \tableofcontents \hypertarget{week-1}{% \section{Week 1}\label{week-1}} \href{http://math.stanford.edu/~vakil/216blog/FOAGnov1817public.pdf}{Link to Notes} \hypertarget{exercise-1.3h-right-exactness-of-tensoring}{% \subsection{Exercise 1.3H: Right Exactness of Tensoring}\label{exercise-1.3h-right-exactness-of-tensoring}} Show that the following endofunctor \begin{align*} F: \rmod &\to \rmod \\ X &\mapsto X\tensor_R N \\ (X\mapsvia{f} Y) &\mapsto (X\tensor_R N \mapsvia{f \tensor \id_N} Y\tensor_R N) \end{align*} is exact. Solution: \begin{quote} Note: to make sense of the functor, we may need to show that there is an isomorphism \begin{align*}\hom_{\rmod}(X, Y) \tensor_R \hom_{\rmod}(A, B) \to \hom_\rmod(X\tensor_R A, Y\tensor_R B).\end{align*} This is what makes taking \(f:X\to Y\) and \(g:A\to B\) and forming \(f\tensor g: X\tensor A \to Y\tensor B\) well-defined? \end{quote} Let \(A\mapsvia{f} B \mapsvia{g} C \to 0\) be an exact sequence, so \begin{itemize} \tightlist \item \(\im f = \ker g\) by exactness at \(B\) \item \(\im g = C\) by exactness at \(C\). \end{itemize} Applying the above \(F\) yields \begin{align*} A\tensor_R N \mapsvia{f\tensor \id_N} B\tensor_R N \mapsvia{g\tensor \id_N} C\tensor_R N \to 0 .\end{align*} We thus need to show \begin{enumerate} \def\labelenumi{\arabic{enumi}.} \tightlist \item Exactness as \(C\tensor_R N\): \(\im(g\tensor \id_N) = C\tensor_R N\), i.e.~this is surjective. \item Exactness at \(B\tensor_R N\): \(\im(f\tensor \id_N) = \ker(g\tensor id_N)\). \end{enumerate} We'll use the fact that every element in a tensor product is a finite sum of elementary tensors. \begin{itemize} \tightlist \item Claim: \(\im(g\tensor \id_N) \subseteq C\tensor_R N\). \begin{itemize} \tightlist \item Let \(b\tensor n \in B\tensor_R N\) be an elementary tensor \item Then \((g\tensor \id_N)(b\tensor n) \definedas g(b) \tensor \id_N (n) = g(b) \tensor n\) \item Since \(\im(g) = C\), there exists a \(c\in C\) such that \(g(b) = c\), so \(g(b) \tensor n = c \tensor n \in C\tensor_R N\) \item Extend by linearity: \end{itemize} \end{itemize} \begin{align*} \qty{g\tensor_R \id_N}\qty{\sum_{i=1}^m r_i \cdot b_i \tensor n_i} =\sum_{i=1}^m (g\tensor \id_N)(r_i\cdot b_i \tensor n_i) \definedas \sum_{i=1}^m g(r_i\cdot b_i) \tensor \id_N(n_i) =_H \sum_{i=1}^m r_i\cdot c_i \tensor n_i \in C\tensor_R N \end{align*} where we've used bilinearity for the first equality, and the equality marked with \(H\) uses above the proof for elementary tensors, and noted that we can pull ring scalars \(r_i\in R\) through \(\rmod\) morphisms. - Claim: \(C \tensor_R N \subseteq \im(g\tensor \id_N)\). - Let \(c\tensor n \in C\tensor_R N\) be an elementary tensor. - Then \(c\in C = \im(g)\) implies \(c = g(b)\) for some \(b\in B\). - So \(c\tensor n = g(b) \tensor n = (g\tensor \id_N)(b\tensor n) \in B\tensor_R N\). - Extend by linearity: \begin{align*} \sum_{i=1}^m r_i\cdot c_i \tensor n_i =_H \sum_{i=1}^m g(r_i\cdot b_i) \tensor n_i = \sum_{i=1}^m (g\tensor \id_N)(r_i\cdot b_i \tensor n_i) = (g\tensor \id_N)\qty{\sum_{i=1}^m r_i\cdot b_i \tensor n_i} .\end{align*} This proves (1). \begin{itemize} \item Claim: \(\im(f\tensor \id_N) \subseteq \ker(g\tensor \id_N)\). \begin{itemize} \tightlist \item Let \(b\tensor n \in \im(f\tensor \id_N)\), we want to show \((g\tensor \id_N)(b\tensor n) = 0 \in C\tensor_R N\). \item Then \(b\tensor n = f(a)\tensor n\) for some \(a\in A\). \item By exactness of the original sequence, \(\im f \subseteq \ker g\), so \(g(f(a)) = 0 \in C\) \item Then \begin{align*} (g\tensor \id_N)\qty{ b \tensor n} = (g\tensor \id_N)(f(a)\tensor n) \definedas g(f(a)) \tensor n = 0\tensor n = 0\in C\tensor_R N \end{align*} where we've used the fact that \(0\tensor x = 0\) in any tensor product. \item Extend by linearity. \end{itemize} \item Claim (\textbf{nontrivial part}): \(\ker(g\tensor \id_N) \subseteq \im(f\tensor \id_N)\). \begin{quote} Note: the problem is that \begin{align*} x\in \ker(g\tensor \id_N) \implies x = \sum_{i=1}^m r_i\cdot b_i \tensor n_i \implies (g\tensor \id_N)\qty{\sum_{i=1}^m r_i\cdot b_i \tensor n_i} = \sum_{i=1}^m r_i\cdot g(b_i) \tensor n_i = 0\in C\tensor_R N \end{align*} \textbf{but} this does not imply that \(g(b_i) = 0\in C\) for all \(i\), which is what you would need to use \(\im f = \ker g\) to write \(g(b_i) = 0\implies \exists a_i, f(a_i) = b_i\) and pull everything back to \(A\tensor_R N\). \end{quote} \begin{itemize} \tightlist \item Strategy: use the first claim and the first isomorphism theorem to obtain this situation: \begin{center} \begin{tikzcd} {B\tensor_R N \over \im(g\tensor_R \id_N)} \ar[r, hook, "i"]\ar[rrr, bend left, dotted, "\alpha"] & {B\tensor_R N \over \ker(g \tensor_R \id_N)} \ar[r, "\cong"] & \im(g\tensor_R \id_N) \ar[equal]{r} & C\tensor_R N \end{tikzcd} \end{center} \item The first injection \(i\) will exist because \(\im(g\tensor_R \id_N) \subseteq \ker(g\tensor_R \id_N)\) by the first claim. \item The middle isomorphism is the first isomorphism theorem. \item The RHS equality follows from surjectivity of \(g\tensor_R \id_N\) \item We then apply a strengthened version of the 1st isomorphism theorem for modules: \end{itemize} \begin{quote} Hungerford Ch.4 Thm 1.7: If \(f:A\to B\) is a \(R\dash\)module morphism and \(C\leq \ker f\) then there is a unique map \(\tilde f: A/C\to B\) which is an isomorphism iff \(f\) is an epimorphism and \(C = \ker f\). Following Hungerford Ch.4 Prop. 5.4, p.210. \end{quote} \begin{itemize} \item Since \(\im(g\tensor_R \id_N)\subseteq \ker(g\tensor_R \id_N)\), by the theorem the map \(\alpha\) exists and satisfies the same formula, i.e.~\(\alpha = \tilde g \tensor \tilde \id_N\) where the tilde denotes the induced map on quotients, so \(\alpha([b\tensor n]) = g(b)\tensor n\). \begin{itemize} \tightlist \item We will show it is an isomorphism, which forces \(\im(g\tensor_R \id_N) \cong \ker(g\tensor_R \id_N)\) by the above theorem. \end{itemize} \item Constructing the inverse map: define \begin{align*} \tilde \alpha\inv: C\times N &\to {B\tensor_R N \over \im(g\tensor_R \id_N) } \\ (c, n) &\mapsto (b \tensor n) \mod \im(g\tensor_R \id_N) \qtext{where} b \in g\inv(c) ,\end{align*} which we will show well-defined (i.e.~independent of choice of \(b\)) and \(R\dash\)linear, lifting to a map \(\alpha\inv\) out of the tensor product by the universal property which is a two-sided inverse for \(\alpha\). \item Well-defined: \begin{itemize} \tightlist \item \(g\inv(b)\) exists because \(g\) is surjective. \item If \(b\neq b'\) and \(g(b') = 0\), then \(0 = g(b) - g(b') = g(b-b')\) so \(b-b' \in \ker g\). \item By the original exactness, \(b-b' \in \im f\) so \(b-b' = f(a)\) for some \(a\in A\). \item Then \(f(a) \tensor n \in \im(f\tensor \id)\) implies \(f(a)\tensor n \equiv 0 \mod \im(f\tensor \id)\). \item Then noting that \(b-b' = f(a) \implies b = f(a) + b'\), working mod \(\im(g\tensor_R \id_N)\) we have \begin{align*} b \tensor n \equiv (f(a) + b') \tensor n \equiv \qty{f(a) \tensor n} + \qty{b' \tensor n} \equiv b'\tensor n .\end{align*} \end{itemize} \item \(R\dash\)linear: \begin{itemize} \tightlist \item ? \end{itemize} \item Two-sided identity: \begin{itemize} \tightlist \item \((\alpha \circ \alpha\inv)(c\tensor n) = \alpha(b\tensor n) = g(b)\tensor n = c\tensor n\), so \(\alpha\circ \alpha\inv = \id\). \item \((\alpha\inv \circ \alpha)([b\tensor n]) = \alpha\inv(g(b) \tensor n) = [b'\tensor n]\) where \(b'\in g\inv(g(b))\) implies \(b'=b\), so \(\alpha\circ\alpha\inv = \id\). \end{itemize} \end{itemize} \end{itemize} \(\qed\) \hypertarget{more-exercises}{% \section{More Exercises}\label{more-exercises}} \hypertarget{k}{% \subsection{1.3.K}\label{k}} \begin{quote} Note: I think this is an exercise about base change. \end{quote} \textbf{Part a}: For \(M\) an \(A\dash\)module and \(\phi: A\to B\) a morphism of rings, give \(B\tensor_A M\) the structure of a \(B\dash\)module and show that it describes a functor \(B\dash\text{Mod}\to A\dash\text{Mod}\). Solution \begin{itemize} \item \(B\tensor_A M\) makes sense: \(B\) is a \((B, A)\dash\)bimodule with the usual multiplication on the left and the right action \begin{align*} A &\to \endo(B) \\ a &\mapsto (b\mapsto b\cdot \phi(a)) .\end{align*} \item \(B\tensor_A M\) is a left \(B\dash\)module via the following action: \begin{align*} B &\to \endo(B\tensor_A M) \\ b_0 &\mapsto (b\tensor m \mapsto b_0 b \tensor m) .\end{align*} \item This describes a functor: \begin{align*} F: A\dash\text{Mod} &\to B\dash\text{Mod} \\ X &\mapsto B\tensor_A X \\ (X\mapsvia{f} Y) &\mapsto (B\tensor_A X \mapsvia{\id_B \tensor f} B\tensor_A Y) .\end{align*} \begin{itemize} \tightlist \item Need to check: \begin{itemize} \tightlist \item Preserves identity morphism, i.e.~\(X\in A\dash\)Mod implies \(F(\id_X) = \id_{F(X)}\) in \(B\dash\)Mod. \item Preserves composition: \(F(f\circ g) = F(f) \circ F(g)\). \end{itemize} \end{itemize} \item Preserving identity morphisms: \begin{itemize} \tightlist \item By construction \(X\selfmap_{\id_X}\) maps to \(B\tensor_A X \mapsvia{\id_B \tensor \id_X} B\tensor_A X\), can argue that this is the identity map for \(B\dash\)modules. \end{itemize} \item Preserving composition: \begin{align*} (X\mapsvia{f} Y \mapsvia{g} Z) \mapsto (B\tensor_A X \mapsvia{ \id_B\tensor f} B\tensor_A Y \mapsvia{\id_B \tensor g} B\tensor_A Z) = (B\tensor_A X \mapsvia{\id_B \tensor (g\circ f)} B\tensor_A Z ) .\end{align*} \end{itemize} \begin{quote} Note: not sure if there's anything to show here. \end{quote} \textbf{Part b}: If \(\psi: A\to C\) is another ring morphism, show that \(B\tensor_A C\) has a ring structure. Solution: \begin{itemize} \item Note \(B\tensor_A C\) makes sense, since \(C\) is a left \(A\dash\)module via \(a\mapsto (c\mapsto \psi(a)c)\). \item Need to define \((B\tensor_A C, P, M)\) such that it's an abelian group under \(P\) (plus), a monoid under \(M\) (multiplication), and left/right distributivity. \item Start by defining on cartesian products: \begin{align*} P: \qty{B\tensor_A C}^{\times 2} &\to B\tensor_A C \\ P\qty{ (b_1 \tensor c_1), (b_2\tensor c_2)} &= (b_1 +_B b_2) \tensor (c_1 +_C c_2) ,\end{align*} \begin{align*} M: \qty{B\tensor_A C}^{\times 2} &\to B\tensor_A C \\ M\qty{ (b_1 \tensor c_1), (b_2\tensor c_2)} &= (b_1 \cdot_B b_2) \tensor (c_1 \cdot_C c_2) .\end{align*} \item Check \(A\dash\)bilinearity: \begin{align*} P(a\cdot (b_1\tensor c_1),\, (b_2\tensor c_2)) &\definedas \qty{ a \cdot (b_1 + b_2)} \tensor (c_1 + c_2) \\ &= \qty{ (b_1 + b_2)} \tensor a\cdot (c_1 + c_2) \quad\text{since $C$ is a left $A\dash$module} \\ &\definedas P((b_1\tensor c_1),\, a\cdot (b_2\tensor c_2)) .\end{align*} \begin{align*} M(a\cdot (b_1\tensor c_1),\, (b_2\tensor c_2)) &\definedas \qty{a\cdot (b_1 \cdot b_2)} \tensor (c_1 \cdot c_2) \\ &= (b_1 \cdot b_2) \tensor \qty{ a\cdot (c_1 \cdot c_2) } \quad\text{since $C$ is a left $A\dash$module} \\ &\definedas M((b_1\tensor c_1),\, a\cdot (b_2\tensor c_2)) .\end{align*} \item So these lift to maps out of \((B\tensor_A C)^{\tensor 2}\). \item \(P\) forms an abelian group: clear because \(+_B, +_C\) do, and commuting is just done within each factor. \item \(M\) forms a monoid: clear for some reason. \item Checking distributivity, claim: it suffices to check on elementary tensors and extend by linearity? \begin{align*} (b_0 \tensor c_0) \cdot \qty{(b_1 \tensor c_1) + (b_2\tensor c_2) } &= (b_0\tensor c_0) \cdot \qty{ (b_1 + b_2) \tensor (c_1 + c_2) } \\ &= (b_0(b_1 + b_2)) \tensor ( c_0(c_1 + c_2)) \\ &= (b_0 b_1 + b_0 b_2) \tensor (c_0 c_1 + c_0 c_2) \\ &= \cdots .\end{align*} \end{itemize} \hypertarget{l}{% \subsection{1.3.L}\label{l}} If \(S\subseteq A\) is multiplicative and \(M\in A\dash\)Mod, describe a natural isomorphism \begin{align*} \eta: (S\inv A)\tensor_A M \to (S\inv M) \end{align*} as both \(S\inv A\dash\)modules and \(A\dash\)modules. Solution \begin{itemize} \tightlist \item Recall the definition \begin{align*} S\inv A\definedas \theset{ {a\over s} \suchthat a\in A, s\in S} / \sim \\ {a_1 \over s_1} \sim {a_2 \over s_2} \iff \exists s\in S \text{ such that } s\qty{ s_2 a_1 - s_1 a_2 } = 0_A .\end{align*} \item Similarly \(S\inv M = \theset{{m\over s}}/\sim\). \end{itemize} The universal property: in \(A\dash\)Mod, \(M\to S\inv M\) is initial among all morphisms \(\alpha: M\to N\) such that \(\alpha(S) \subseteq N\units\): \begin{center} \begin{tikzcd} & S\inv M \ar[d, dotted, "{\exists ! \tilde\alpha}"] \\ M\ar[ru, "S\inv \cdot"]\ar[r, "\alpha"] & N \end{tikzcd} \end{center} \begin{quote} Strategy: define a map \(M\to S\inv A \tensor_A M\) such that \(S\) is invertible in the image to obtain a map? Show they satisfy the same universal property? \end{quote} \begin{itemize} \item Since \(M \in A\dash\)Mod, we have an action \(a\cdot m\), so define \begin{align*} \eta: (S\inv A)\times M &\to (S\inv M) \\ \qty{ {a\over s}, m } &\mapsto {a\cdot m \over s } .\end{align*} \item The tensor product \(S\inv A \tensor_A M\) makes sense. \begin{itemize} \tightlist \item \(S\inv A\) is a right \(A\dash\)module by \(a_0 \mapsto \qty{ {a\over s} \mapsto {a_0 a \over s}}\). \item \(S\inv M\) is a left \(A\dash\)module by \(a_0 \mapsto (m \mapsto a_0 \cdot m)\) where the action comes from the \(A\dash\)module structure of \(M\). \end{itemize} \item The map makes sense as an \(A\dash\)module morphism \begin{itemize} \tightlist \item \(S\inv A \tensor_A M\) is a left \(A\dash\)module by \(a_0 \mapsto \qty{{a\over s}\tensor m \mapsto {a_0 a \over s} \tensor m}\) \item \(S\inv M\) is a left \(A\dash\)module by \(a_0 \mapsto \qty{ {m\over s } \mapsto {a_0 \cdot m \over s}}\) using the \(A\dash\)module structure on \(M\). \end{itemize} \item The map makes sense as an \(S\inv A\dash\)module morphism \begin{itemize} \tightlist \item \(S\inv A \tensor_A M\) is a left \(S\inv A\dash\)module by \({a_0\over s_0} \mapsto \qty{ {a\over s}\tensor m \mapsto {a_0 a \over s_0 s} \tensor m }\) \item \(S\inv M\) is a left \(S\inv A\dash\)module by \({a_0\over s_0} \mapsto \qty{{m \over s} \mapsto {a_0 \cdot m \over s_0 s} }\) by the \(A\dash\)module structure on \(M\). \end{itemize} \item Well-defined: ? \item \(A\dash\)bilinear: let \(r\in A\), then \begin{align*} \eta\qty{r \cdot {a\over s}, m} &\definedas \eta\qty{{r\cdot a\over s}, m} \\ &\definedas {\psi(r\cdot a)(m) \over s} \\ &= {r\cdot \psi(a)(m) \over s} \quad\text{since $\psi$ is a ring morphism} \\ &= {\psi(a)(r\cdot m) \over s} \quad\text{since $\psi(a)$ is a ring morphism} \\ &\definedas \eta\qty{ {a\over s}, r\cdot m} .\end{align*} So this lifts to a map out of the tensor product. \item \(S\inv A\dash\)bilinear? \end{itemize} \hypertarget{p}{% \subsection{1.3.P}\label{p}} Show that the fiber product over the terminal object is the cartesian product. Solution: \begin{itemize} \tightlist \item Recall definition: \(T\) is terminal iff every object \(X\) admits a morphism \(X\to T\). \item Strategy: use both universal products to produce an isomorphism \item Let \(\pr_X, \pr_Y\) by the cartesian product projections, and \(\pr_X^T, \pr_Y^T\) be the fiber product projections \item Let \(T_X, T_Y\) be the maps \(X\to T, Y\to T\). \item Since \(X\cross Y\) is an object in this category, it admits one unique map to \(T\) \end{itemize} \begin{center} \begin{tikzcd} X\cross Y\ar[r, "\pr_Y"]\ar[d, "\pr_X"']\ar[dr, "T_{X\cross Y}"] & Y\ar[d, "T_Y"] \\ X\ar[r, "T_X"'] & T \end{tikzcd} \end{center} \begin{itemize} \tightlist \item But now \(T_Y \circ \pr_Y: X\cross Y \to T\) is another such map, so it must equal \(T_{X\cross Y}\). \item Similarly \(T_X \circ \pr_X\) is equal to \(T_{X\cross Y}\). \item Thus \(T_Y \circ \pr_Y = T_X \circ \pr_Y\), which is part of the universal property for \(X\cross_T Y\). \item By the universal property of \(X\cross Y\), for every \(W\) admitting maps to \(X, Y\) we get the following \(h_0\): \begin{center} \begin{tikzcd} W \ar[drr, bend left]\ar[rdd, bend right]\ar[dr, dotted, "\exists ! h_0"] & & \\ & X\cross Y\ar[r, "\pr_Y"]\ar[d, "\pr_X"] & Y\ar[d, "T_Y"] \\ & X\ar[r, "T_X"] & T \end{tikzcd} \end{center} \begin{quote} Note that \(T\) doesn't matter in this particular diagram. \end{quote} \item This gives us the LHS diagram, the RHS comes from the universal property of \(X\cross Y\): \begin{center} \begin{tikzcd} X\cross_T Y\ar[drr, "\pr_Y^T", bend left]\ar[rdd, "\pr_X^T", bend right]\ar[dr, dotted, "\exists ! h_0"] & & \\ & X\cross Y\ar[r, "\pr_Y"]\ar[d, "\pr_X"] & Y\ar[d, "T_Y"] \\ & X\ar[r, "T_X"] & T \end{tikzcd} \begin{tikzcd} X\cross Y\ar[drr, "\pr_Y", bend left]\ar[rdd, "\pr_X", bend right]\ar[dr, dotted, "\exists ! h_1"] & & \\ & X\cross_T Y\ar[r, "\pr_Y^T"]\ar[d, "\pr_X^T"] & Y\ar[d, "T_Y"] \\ & X\ar[r, "T_X"] & T \end{tikzcd} \end{center} \item By commutativity, \(h_0 \circ h_1 = \id_{X\cross Y}\) and vice-versa? \end{itemize} \hypertarget{q}{% \subsection{1.3.Q}\label{q}} Show that if the two squares in this diagram are cartesian, then then outer square is also cartesian: \begin{center} \begin{tikzcd} U \ar[r]\ar[d] & V\ar[d] \\ W \ar[r]\ar[d] & X\ar[d] \\ Y \ar[r] & Z \end{tikzcd} \end{center} Solution: \begin{itemize} \tightlist \item Need to show that given two maps \(R\to V\) and \(R\to Y\) such that \((V\to Z) \circ (U\to V) = (Y\to Z) \circ (R\to Y)\), then there is a unique map \(R\to U\) giving a commuting diagram: \begin{center} \begin{tikzcd} U\ar[drr, bend left] \ar[rdd, bend right] & & \\ & R\ar[ul, dotted, "\exists !\, ?"] \ar[r]\ar[d] & V\ar[d] \\ & Y \ar[r] & Z \end{tikzcd} \end{center} \item Applying the bottom square: \begin{itemize} \tightlist \item Need to produce maps \(R\to X\) and \(R\to Y\) \item We're given a map \(R\to Y\) by assumption. \item We can build a map \(R\to X\) by taking \((V\to X) \circ (R\to V)\). \item We then get a map \(R\to W\): \begin{center} \begin{tikzcd} W\ar[drr, bend left] \ar[rdd, bend right] & & \\ & R\ar[ul, dotted, "\exists !"] \ar[r]\ar[d] & X\ar[d] \\ & Y \ar[r] & Z \end{tikzcd} \end{center} \end{itemize} \item Applying the top square: \begin{itemize} \tightlist \item We have a map \(R\to V\) by assumption \item We have a map \(R\to W\) from step 1 \item We have maps \(V\to X\) and \(W\to X\) from the top square \item We thus obtain \begin{center} \begin{tikzcd} U\ar[drr, bend left] \ar[rdd, bend right] & & \\ & R\ar[ul, dotted, "\exists !"] \ar[r]\ar[d] & V\ar[d] \\ & W \ar[r] & X \end{tikzcd} \end{center} \end{itemize} \end{itemize} \bibliography{/home/zack/Notes/library.bib} \end{document}